Analisa sistem perawatan pada mesin las MIG dengan metode Failure Mode and Effect Analysis: Studi kasus di PT. TE - Alloysius Vendhi Prasmoro (Universitas Mercu Buana, 2020)
Maintenance is a process that is done to maintain the reliability, availability and the nature of being able to take care of the components or machines. Maintenance program that will effectively and efficiently support the increase in productivity of production systems. But often ignored the needs of actual maintenance program of components or machines. To get the program effective and efficient maintenance required maintenance study based on reliability. Reliability Centered Maintenance (RCM) is a systematic risk-based analysis to create a maintenance method accurate, focused, and optimal with the aim of achieving optimal reliability of assets. RCM studies have been done on the machinery industry, one welding machine industry, carrosserie. The study was conducted by following these RCM, which is the determination of the scope of the study, Failure Mode and Effect Analysis (FMEA), and the determination of the maintenance strategy. Analysis of the risk based on risk matrix drawn up through consensus of all stakeholders. Risk matrix covers the areas the incidence (occurrence), detection, as well as the level of risk (severity). Subsequently based on this calculated risk matrix Risk Priority Number (RPN). Based on the RPN value, a maintenance strategy is proposed for each type of failure mode. The whole process is aided by the use of RCM software Minitab 18 made specifically for this purpose. This study results that the value of the RPN for all equipment ranges from 72 to 900.Study of the RCM have also managed to establish a maintenance strategy appropriate for each failure mode, which provided the basis for drafting the new maintenance program.